Comparing Various GnRH Protocols to Improve Fertility Outcomes in Patients with Adenomyosis: A Qualitative Systematic Review - Sofi Sumarlin; Imelda E B Hutagaol; Muhammad Yusuf; Nicko Pisceski Kusika Saputra; Silvi Angelia May Purba; Arya Marganda Simanjuntak (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Adenomyosis impairs fertility through chronic inflammation and endometrial damage. While IVF with GnRH modulation is used to improve outcomes, no universal protocol exists. This study compares long versus short GnRH agonist protocols for improving fertility in adenomyosis patients.Methods: This qualitative systematic review [CRD420251272312] searched databases like PubMed and Semantic Scholar in November 2025. It included English-language observational studies or RCTs involving human samples, while excluding duplicates and incomplete manuscripts.Results: From 858 abstracts, three studies were analyzed. No method significantly altered oocyte count or myometrial thickness. Ultra-long and long GnRH agonist protocols showed higher pregnancy rates and lower miscarriage risks, whereas antagonist and short agonist protocols had poorer outcomes.Conclusions: Ultra-long and long GnRH agonist protocols are promising for adenomyosis, but these preliminary results from limited studies require validation through larger randomized controlled trials addressing confounding factors.Perbandingan Variasi Protokol GnRH untuk Meningkatkan Hasil Kesuburan pada Pasien dengan Adenomiosis: Sebuah Tinjauan Sistematis KualitatifAbstrakPendahuluan: Adenomiosis mengganggu kesuburan melalui peradangan kronis dan kerusakan endometrium. Meskipun IVF dengan modulasi GnRH digunakan untuk meningkatkan hasil, tidak ada protokol universal yang ada. Studi ini membandingkan protokol agonis GnRH panjang versus pendek untuk meningkatkan kesuburan pada pasien adenomiosis.Metode: Tinjauan sistematis kualitatif ini [CRD420251272312] mencari basis data seperti PubMed dan Semantic Scholar pada November 2025. Ini mencakup studi observasional atau RCT berbahasa Inggris yang melibatkan sampel manusia, sambil mengecualikan duplikat dan manuskrip yang tidak lengkap.Hasil: Dari 858 abstrak, tiga studi dianalisis. Tidak ada metode yang secara signifikan mengubah jumlah oosit atau ketebalan miometrium. Protokol agonis GnRH ultra-panjang dan panjang menunjukkan tingkat kehamilan yang lebih tinggi dan risiko keguguran yang lebih rendah, sementara protokol antagonis dan agonis pendek memiliki hasil yang lebih buruk.Kesimpulan: Protokol agonis GnRH ultra-panjang dan panjang menjanjikan untuk adenomiosis, tetapi hasil awal dari studi terbatas ini memerlukan validasi melalui uji coba terkontrol acak yang lebih besar yang membahas faktor-faktor perancu.